EFFECT OF BALLAST POSITION ON VERTICAL STABILITY AND EFFICIENCY OF A SMALL-SCALE BUOYANCY-DRIVEN UNDERWATER GLIDER - Arie Sukma Jaya; Yusuf Arindyatama Putra (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2026)
Underwater gliders rely on buoyancy-driven motion for long-duration, energy-efficient ocean monitoring, but their stability and performance depend strongly on mass distribution. This study evaluates how ballast position affects vertical dynamics and buoyancy-driven energy-conversion efficiency in a 50 cm cylindrical, syringe-based buoyancy glider tested in a laboratory tank under sinking and floating conditions. Three ballast position ratios (λb = 0.2, 0.4, and 0.5) were selected (forward, intermediate, near-midpoint) to capture the transition toward stable vertical motion under reproducible, prototype-constrained conditions. Vertical velocity, buoyancy-driven energy-conversion efficiency (defined as useful buoyancy power divided by electrical input power), and orientation angles (pitch and roll) were measured using video tracking and an MPU6050 sensor. In this work, maximum efficiency refers to the ballast configuration that maximizes this energy-conversion ratio while exhibiting stable pitch and roll, which indicate vertical-motion stability. Results show that forward ballast (λb = 0.2) produced steep pitch angles exceeding 100°, reduced displacement to 15 cm, and yielded low efficiency ( 13–15%). Shifting the ballast aft improved performance, with the midpoint configuration (λb = 0.5) achieving near-vertical alignment, symmetric ascent and descent, higher velocity ( 0.045 m/s), and the highest efficiency ( 23%). The relative roll response remained more stable across all cases, confirming that pitch dynamics dominate performance. The study concludes that optimal ballast placement near the midpoint maximizes stability and buoyancy-driven energy-conversion efficiency, offering a simple yet effective design principle for improving small-scale buoyancy-driven gliders.